1970
DOI: 10.4314/ejhs.v29i4.10
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Risk Factors Associated with Nasal Methicillin- Resistant Staphylococcus Aureus Colonization among Children in a Tertiary Hospital in Nigeria

Abstract: BACKGROUND: Nasal methicillin-resistant Staphylococcus aureus (MRSA) colonization is of public health concern due to increased risk of developing invasive infections and the therapeutic challenges. This concern is more among the vulnerable group. We determined the prevalence and associated risk factors of MRSA nasal carriage among children in a tertiary hospital in Nigeria.METHOD: We conducted a hospital-based, cross-sectional study among 300 children attending the outpatient clinic of a tertiary hospital recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Así mismo, Nelwan et al (2018), en Indonesia en 384 pacientes adultos (antes de someterse a un procedimiento quirúrgico electivo), encontraron que se detectó S. aureus en el 15,6% de ellos y 0,8% fueron SARM. Además, Tuta et al (2019), en Nigeria, encontraron que entre 300 niños que asistían a la consulta externa, el 36,3% estaba colonizado por S. aureus y el 5,3% eran SARM. De igual manera, Matsumoto et al (2018), en Japón, en un hospital con una alta densidad de infección, en 157 pacientes encontraron que S. aureus resistente a la meticilina prevaleció en el 1,9% de ellos.…”
Section: Fajardo and Gainesunclassified
“…Así mismo, Nelwan et al (2018), en Indonesia en 384 pacientes adultos (antes de someterse a un procedimiento quirúrgico electivo), encontraron que se detectó S. aureus en el 15,6% de ellos y 0,8% fueron SARM. Además, Tuta et al (2019), en Nigeria, encontraron que entre 300 niños que asistían a la consulta externa, el 36,3% estaba colonizado por S. aureus y el 5,3% eran SARM. De igual manera, Matsumoto et al (2018), en Japón, en un hospital con una alta densidad de infección, en 157 pacientes encontraron que S. aureus resistente a la meticilina prevaleció en el 1,9% de ellos.…”
Section: Fajardo and Gainesunclassified
“…Methicillin-resistant Staphylococcus aureus (MRSA) is an important bacterial pathogen causing a number of community-acquired and nosocomial infections, including septicemia, skin and soft tissue infections, osteomyelitis, and endocarditis ( 1 ). It is a global health problem and the prevalence of MRSA in India ranges from 25–50% ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the MRSA colonization rate, producing infections, has dramatically increased among different populations, the most susceptible being children and elderly >85 years of age. 10 , 11 As such, active screening of MRSA strains has become both necessary and urgent. In this study, we demonstrated that the active screening of nasal vestibular swabs in ICU patients can successfully achieve early detection, early intervention, and early treatment of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%